Applied Pharmacometrics - Schmidt, Stephan; Derendorf, Hartmut; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This comprehensive volume provides an update on the current state of pharmacometrics in drug development. It consists of nineteen chapters all written by leading scientists from the pharmaceutical industry, regulatory agencies and academia. After an introduction of the basic pharmacokinetic and pharmacodynamic concepts of pharmacometrics in drug development, the book presents numerous examples of specific applications that utilize pharmacometrics with modeling and simulations over a variety of therapeutic areas, including pediatrics, diabetes, obesity, infections, psychiatrics, Alzheimer’s disease, and dermatology, among others. The examples illustrate how results from all phases of drug development can be integrated in a more timely and cost-effective process. Applying pharmacometric decision tools during drug development can allow objective, data-based decision making. At the same time, the process can identify redundant or unnecessary experiments as well as some costly clinical trials that can be avoided. In addition to cost saving by expedited development of successful drug candidates, pharmacometrics has an important economic impact in drug product selection.  Unsuccessful drug candidates can be identified early and discontinued without expending efforts required for additional studies and allocating limited resources. Hence, pharmacometric modeling and simulation has become a powerful tool to bring new and better medications to the patient at a faster pace and with greater probability of success.
1 Introduction to Pharmacometrics and Quantitative Pharmacology with an Emphasis on Physiologically Based Pharmacokinetics -- 2 Personalized Medicine – Integrating Individual Exposure and Response Information at the Bedside -- 3 Pharmacometrics in Pediatrics -- 4 Pharmacometrics in Chronic Kidney Disease -- 5 Drug-Disease Model-Based Development of Therapeutic Agents for Treatment of Diabetes -- 6 Applied Pharmacometrics in the Obese Population -- 7 Pharmacometrics in Cardiovascular Safety -- 8 Pharmacometrics in Bacterial Infections -- 9 Pharmacometrics in Viral Infections -- 10 Applied Antifungal Pharmacometrics: Fluconazole and Echinocandins in the Treatment of Candidemia and Invasive Candidiasis -- 11 Pharmacometrics and Tuberculosis -- 12 Pharmacometrics in Pulmonary Diseases -- 13 State-of-the-Art Pharmacometric Models in Osteoporosis -- 14 Pharmacometrics in Psychiatric Diseases -- 15 Clinical Trial Simulation in Alzheimer’s Disease -- 16 Pharmacometric Applications in Inflammation -- 17 Pharmacometrics in Dermatology -- 18 Pharmacometrics in Pain Management -- 19 Pharmacometrics of Hyperlipidemia.
Keywords: Pharmaceutical technology; Pharmaceutical Sciences/Technology.